Antibodies to Plasmodium falciparum merozoite surface protein-1p19 malaria vaccine candidate induce antibody-dependent respiratory burst in human neutrophils. (December 2015) - Joos, Charlotte; Varela, Marie-Louise; Mbengue, Babacar; Mansourou, Annick; Marrama, Laurence; Sokhna, Cheikh; Tall, Adama; Trape, Jean-François; Touré, Aissatou; Mercereau-Puijalon, Odile; Perraut, Ronald
Abstract Background Identification of plasmodial antigens targeted by protective immune mechanisms is important for malaria vaccine development. Among functional assays, the neutrophil antibody-dependent respiratory burst (ADRB) induced by opsonizedPlasmodium falciparum merozoites has been correlated with acquired immunity to clinical malaria in endemic areas, but the target merozoite antigens are unknown. Here, the contribution of antibodies to the conserved C-terminal domain of theP. falciparum merozoite surface protein-1 (PfMSP1p19) in mediating ADRB was investigated in sera from individuals living in two Senegalese villages with differing malaria endemicity. Methods Anti-PfMSP1p19 antibody levels in sera from 233 villagers were investigated and the involvement of anti-PfMSP1p19 antibodies in ADRB was explored in a subset of samples using (1) isogenicP. falciparum parasite clones expressingP. falciparum orPlasmodium chabaudi MSP1p19; (2) PfMSP1p19-coated plaque ADRB; and, (3) ADRB triggering using sera depleted from PfMSP1p19 antibodies by absorption onto the baculovirus recombinant antigen. Results ADRB activity correlated with anti-PfMSP1p19 IgG levels (P < 10−3 ). A substantial contribution of PfMSP1p19 antibody responses to ADRB was confirmed (P < 10−4 ) in an age-adjusted linear regression model. PfMSP1p19 antibodies accounted for 33.1 % (range 7–54 %) and 33.2 % (range 0–70 %) of ADRB activity evaluated using isogenic merozoites (P < 10−3 ) and depleted sera (P = 0.0017), respectively. Coating of PfMSP1p19 on plates induced strong ADRB in anti-PfMSP1p19-positive sera. Conclusion These data show that naturally acquiredP. falciparum MSP1p19 antibodies are potent inducers of neutrophil ADRB and support the development of PfMSP1p19-based malaria vaccine using ADRB assay as a functional surrogate for protection.